A-series agent A-234: initial in vitro and in vivo characterization - Hrabinova, Martina; Pejchal, Jaroslav; Hepnarova, Vendula; Muckova, Lubica; Junova, Lucie; Opravil, Jakub; Zdarova Karasova, Jana; Rozsypal, Tomas; Dlabkova, Alzbeta; Rehulkova, Helena; Kucera, Tomas; Vecera, Zbyněk; et al. (Archives of toxicology, 2024)
A-series agent A-234 belongs to a new generation of nerve agents. The poisoning of a former Russian spy Sergei Skripal and his daughter in Salisbury, England, in March 2018 led to the inclusion of A-234 and other A-series agents into the Chemical Weapons Convention. Even though five years have already passed, there is still very little information on its chemical properties, biological activities, and treatment options with established antidotes. In this article, we first assessed A-234 stability in neutral pH for subsequent experiments. Then, we determined its inhibitory potential towards human recombinant acetylcholinesterase (HssAChE; EC 3.1.1.7) and butyrylcholinesterase (HssBChE; EC 3.1.1.8), the ability of HI-6, obidoxime, pralidoxime, methoxime, and trimedoxime to reactivate inhibited cholinesterases (ChEs), its toxicity in rats and therapeutic effects of different antidotal approaches. Finally, we utilized molecular dynamics to explain our findings. The results of spontaneous A-234 hydrolysis showed a slow process with a reaction rate displaying a triphasic course during the first 72 h (the residual concentration 86.2%). A-234 was found to be a potent inhibitor of both human ChEs (HssAChE IC50 = 0.101 ± 0.003 µM and HssBChE IC50 = 0.036 ± 0.002 µM), whereas the five marketed oximes have negligible reactivation ability toward A-234-inhibited HssAChE and HssBChE. The acute toxicity of A-234 is comparable to that of VX and in the context of therapy, atropine and diazepam effectively mitigate A-234 lethality. Even though oxime administration may induce minor improvements, selected oximes (HI-6 and methoxime) do not reactivate ChEs in vivo. Molecular dynamics implies that all marketed oximes are weak nucleophiles, which may explain the failure to reactivate the A-234 phosphorus-serine oxygen bond characterized by low partial charge, in particular, HI-6 and trimedoxime oxime oxygen may not be able to effectively approach the A-234 phosphorus, while pralidoxime displayed low interaction energy. This study is the first to provide essential experimental preclinical data on the A-234 compound.
Keywords: Cholinesterase Reactivators; acetylcholinesterasa; Taurine; pralidoximové sloučeniny; lidé; cholinesterasové inhibitory; fosfor; oximy; krysa rodu Rattus; reaktivátory cholinesterasy; Butyrylcholinesterase; Humans; Phosphorus; Hydrolysis; Therapy; antidota; Antidotes; trimedoxim; Oximes; Trimedoxime; Acetylcholinesterase; butyrylcholinesterasa; Reactivation; zvířata; Nerve agent A-234; Acute toxicity; Rats; Animals; Pralidoxime Compounds; Oxygen; taurin; pyridinové sloučeniny; kyslík; Cholinesterase Inhibitors; Pyridinium Compounds